Development of a flipped classroom learning with a drill and practice approach to improve the students psychomotor skills in class motorbike engineering - Soepriyanto, Yerry; Ulfa, Saida; Negara, Nur Alamsyah Surya (Univeritas Papua, 2025)
This study aims to develop learning to improve psychomotor skills in the practical subjects of class XI motorcycle engineering students. The development in this study uses the ADDIE model. The research subjects consisted of three experts and 33 class XI motorcycle engineering students in the learning design trial. Data collection used a content expert validation questionnaire, a media expert validation questionnaire, a learning design expert validation questionnaire, and a test. Data processing was carried out by calculating scores and validity percentages, while the influence test used the t test. The findings of the validity level of the development of flipped class learning designs with the drill and practice approach received an assessment from content experts of 100% (very valid), media experts of 100% (very valid), and learning design experts of 97% (very valid). Furthermore, the findings of the influence test using the t test obtained a significance value of 0.000. From the calculation results, the significance of 0.000 is less than 0.05, meaning that there is a significant difference in the use of a flipped class learning design with a real and practice approach and not using a flipped class with a drill and practice approach.